2009
DOI: 10.1124/mol.109.058701
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol (4,5)-Bisphosphate Regulation ofN-Methyl-d-aspartate Receptor Channels in Cortical Neurons

Abstract: The membrane phospholipid phosphatidylinositol (4,5)-bisphosphate (PIP 2 ) has been implicated in the regulation of several ion channels and transporters. In this study, we examined the impact of PIP 2 on N-methyl-D-aspartate receptors (NMDARs) in cortical neurons. Blocking PIP 2 synthesis by inhibiting phosphoinositide-4 kinase, or stimulating PIP 2 hydrolysis via activation of phospholipase C (PLC), or blocking PIP 2 function with an antibody caused a significant reduction of NMDAR-mediated currents. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 72 publications
(102 reference statements)
1
26
0
Order By: Relevance
“…Examples of PIP 2 -dependent ion channels and receptors include inwardly rectifying K ϩ channels (Kir) (3,4), voltagegated K ϩ channels (Kv) (5)(6)(7)(8), voltage-gated Ca 2ϩ channels (9), TRP channels (10), and NMDA receptors (11,12).…”
mentioning
confidence: 99%
“…Examples of PIP 2 -dependent ion channels and receptors include inwardly rectifying K ϩ channels (Kir) (3,4), voltagegated K ϩ channels (Kv) (5)(6)(7)(8), voltage-gated Ca 2ϩ channels (9), TRP channels (10), and NMDA receptors (11,12).…”
mentioning
confidence: 99%
“…The dephosphorylated cofilin binds to F-actin, leading to actin severing and depolymerization (Morgan et al, 1993). Our previous studies have shown that cofilin-regulated actin dynamics is critically involved in the regulation of NMDAR trafficking and function (Mandal and Yan, 2009;Gu et al, 2012). Since the Ser3 residue of cofilin acts as a switch for actin assembly (F-actin stabilization) and disassembly (F-actin severing), we used a Ser3-phosphorylated cofilin peptide (Aizawa et al, 2001;Zhou et al, 2004) to inhibit the activation of endogenous cofilin.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking PIP 2 reduces NMDAR-mediated currents, whereas application of PIP 2 enhances these currents (Mandal and Yan, 2009). Moreover, cofilin, an actin depolymerizing factor which links actin and PIP 2 is required for NMDARs regulation, suggesting that a decrease in PIP 2 leads to cofilin release and actin depolymerization, which in turn promotes NMDARs internalization (Mandal and Yan, 2009).…”
Section: Regulation Of Nmdars Function Is a Complex Process Involvingmentioning
confidence: 99%
“…Moreover, cofilin, an actin depolymerizing factor which links actin and PIP 2 is required for NMDARs regulation, suggesting that a decrease in PIP 2 leads to cofilin release and actin depolymerization, which in turn promotes NMDARs internalization (Mandal and Yan, 2009). Active myosin light chain kinase enhances NMDARs-mediated whole-cell and synaptic currents, increasing actin-myosin contractility, which leads to increased membrane tension on NMDARs or to altered physical relationships between NMDAR anchored proteins, such as PSD-95 (Kornau et al, 1995) and cytoskeleton (Lei et al, 2001).…”
Section: Regulation Of Nmdars Function Is a Complex Process Involvingmentioning
confidence: 99%
See 1 more Smart Citation